26. EVALUATION OF EARLY RESULTS OF ENDOVENOUS LASER TREATMENT FOR INFERIOR EXTREMITY SUPERFICIAL VENOUS INSUFFICIENCY AT QUANG NAM CENTRAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Background: Varicose veins of the lower limbs is a common disease. The disease greatly affects the patient's aesthetics and quality of life. At Quang Nam Central General Hospital, treatment of superficial lower limb venous insufficiency with endovenous LASER ablation was performed for the first time in November 2019. Up to now, this treatment method has gradually become more popular.Objective: Evaluate early results (after 4 weeks) of treating superficial lower limb venous insufficiency with endovenous LASER ablation.Subjects and methods: Prospective intervention. The study will be conducted in 18 months (May 2022-October 2023). All patients meeting for selection criterion were treated with endovenous LASER ablation. Evaluating results after 4 weeks through clinical examination to evaluate symptom improvement and venous Doppler ultrasound to check embolization effectiveness, and evaluating complications of treatment.Results: The median length of the great saphenous vein segment treated with endovascular LASER was 42 cm. The length of the small saphenous vein lasered is 18 cm. The average LASER energy used in the study for the treatment of greater saphenous vein insufficiency was 61.99 ± 5.63 J/cm, for the small saphenous vein it was 68.3 J/cm. Change in CEAP-C clinical grading after intravascular LASER: CEAP-C2 decreased from 61.8% to 14.7%; CEAP-C3 decreased from 11.8% to 0%; CEAP-C4a decreased from 14.7% to 5.9%; CEAP-C4c decreased from 11.8% to 2.9%. The median VCSS score after intervention decreased by 3 points compared to before intervention, this difference is statistically significant. Vein diameter after intervention decreased statistically significantly compared to before intervention (from 5.86 mm before intervention to 3 mm after intervention). After intervention, all saphenous veins treated with endovascular LASER were completely occluded and had no flow. The most common complications after endovenous LASER intervention are pain along the vein path (88.2%) and bruising along the LASER vein path (67.6%). These complications are usually mild and recover quickly.Conclusion: Endovenous LASER is a safe, effective, and aesthetic treatment method for superficial varicose veins of the lower limbs.
Keywords: LASER nội tĩnh mạch